2010
DOI: 10.1016/j.rmed.2009.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability in the severity and outcome of community-acquired pneumonia

Abstract: Our study does not support a role for the controversial studied polymorphisms of the TNF, LTA, IL6 and IL1RN genes in the susceptibility or outcome of CAP. A protective role of heterozygosity for the functionally relevant TNFRSF1B+676 polymorphism in the outcome of CAP was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 40 publications
3
60
0
1
Order By: Relevance
“…Another finding that we could not replicate was the increased risk of sepsis associated with the À863 A TNF allele in an adult study [45]. A recent study evaluating 1136 adult Caucasian septic patients did not report any association between SNP TNF-308 and sepsis mortality [17]. Similar results were reported from two Brazilian studies with adult patients [18,19].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Another finding that we could not replicate was the increased risk of sepsis associated with the À863 A TNF allele in an adult study [45]. A recent study evaluating 1136 adult Caucasian septic patients did not report any association between SNP TNF-308 and sepsis mortality [17]. Similar results were reported from two Brazilian studies with adult patients [18,19].…”
Section: Discussionsupporting
confidence: 69%
“…Single nucleotide polymorphisms (SNPs) in inflammatory cytokine genes such as those coding for TNF and LTA have been extensively evaluated in adults [12][13][14][15][16][17], providing good markers for severity in adult sepsis. A recent meta-analysis has confirmed an increased risk of sepsis in carriers of the A allele for the TNF-308 G > A SNP [6] and AA genotype for LTA + 252A > G SNP [7].…”
Section: Introductionmentioning
confidence: 99%
“…However several studies found no association between TNFA-308 and susceptibility or outcome of CAP [Sole-Violan et al, 2009;Kinder et al 2007;Waterer et al 2001b]. A two-SNP haplotype including TNFA-308 Ã A and TNFA-238 Ã A (rs361525) may be a better predictor of higher mortality in sepsis [Henckaerts et al 2009;Pappachan et al 2009 LTA is adjacent to TNF on chromosome 6 and carriage of the A allele at LTAþ252 (G/A, rs909253) was one of the first genetic factors associated with death from septic shock [Stuber et al 1996].…”
Section: Pro-inflammatory Cytokinesmentioning
confidence: 99%
“…Heterozygosity is protective against the outcome of CAP [Sole-Violan et al 2009] Notation of alleles is gene-nucleotide position (allele 1/allele 2), with allele 1 being the most frequent in the population (wild-type). Amino acid changes are presented where they arise.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo demonstration of the role of G allele, with consequences in increasing the inflammatory response mediated by elevated cytokines circulating levels, underlined the possible involvement of variations within the regulatory part of the IL-6 gene in sepsis incidence and outcome (10,11). Results in the literature are still inconclusive, some authors associating this SNP with an increased sepsis risk (10,12,13), while others invalidating such associations (14,15) or pointing out to its relevance in combination with other gene polymorphisms (16).…”
Section: Introductionmentioning
confidence: 99%